A New Validated Stability-Indicating RP-HPLC Method for the Estimation of Pitavastatin in Tablet Dosage Forms - K.Sujatha; J.V.L.N.Seshagiri Rao (International Journal of Pharmacy and Analytical Research, 2014)
An accurate and stability - indicating high performance liquid chromatographic method was developed for quantification of pitavastatin in its tablet dosage forms. Ideal separation of the drug was achieved on an Agilent Eclipse XDB C18 column (150 x 4.6 mm; 5) by eluting with a mobile phase consisting of a mixture of phosphate buffer (pH 3.4) and acetonitrile (65:35 v/v) at a flow rate of 0.9 mL/min. The drug in the eluates was monitored at 244 nm. Under optimized conditions, the retention time obtained for the drug was 3.905 min. The calibration plot was linear in the concentration range of 25 - 150 µg/mL of the drug. The validation of the method was done by following the ICH guidelines. The proposed method could be applied for determination of pitavastatin in its tablet dosage forms without any interference from normal excipients. The method thus, is suitable for routine quality control analysis of pitavastatin.